Guarantees of the worker's right to the principle of equality and equal opportunities in the Iraqi labor law - رشيد, صبا نعمان; راشد, علي كريدي (Journal of Legal Sciences, 2019)
The principle of equality in human life is one of the noblest principles ever found. These principles have been planted in the conscience and conscience of man, and it is the principle that is considered to be an inextricable right with the existence of human in the collective relations between humans in general and members of a group of groups or conglomerates unintentionally organized but created by circumstances. Accordingly, all international and domestic legislations considered it to be a human right, especially in relation to equality in the right to work, equality in other rights and what is associated with the remuneration of work (wages) and related to its attachments and leave. The Labor Law No. 37 of 2015, In Chapter III. This chapter, entitled "Basic Principles and on the basis of absolute equality" in article 4, which states that "Work shall be the right of every citizen capable of it, and the State shall endeavor to provide it on the basis of equal opportunity without discrimination of any kind." Article Equal to workers who are able to work and this is called absolute equality. At the end of the process, the relative equality of those whose chances are equal is determined, and in both cases they are governed by the principle of non-discrimination. This is what was stated in the Iraqi Constitution of 2005, consistent with and consistent with the law. Article 22 (1) states that "work is a right for all Iraqis to ensure a dignified life." In this regard, (Equality before the law among all Iraqis) in conformity with the Constitution (2005) and other times have affirmed and recognized the relative equality of equal opportunity and the principle of equal opportunities is the result of the principle of equality and the principle of equal opportunities The principle of equality which has been given for a year is enshrined in article 8 (a) (B) of the Labor Code, which states that "This Act prohibits any violation or violation of the principle of equal opportunities and equal treatment for any reason, and in particular discrimination between workers, whether directly or indirectly, in respect of vocational training, employment or "All that was said was the work on absolute equality or relative or realistic equality that we presented in the body of the research was proportionate and consistent with the provisions of the Constitution of Iraq for the year2005.